Understanding of the nanosize effect on the structure and electrochemistry of V2O5 obtained via fluorine chemistry. (2018) - Huo, D.; Laïk, B.; Bonnet, P.; Guerin, K.; Cenac-Morthe, C.; Baddour-Hadjean, R.; Pereira-Ramos, J.P.
Abstract: We demonstrate the benefit of an original vanadium pentoxide (V2 O5 ) nanostructuration on the electrochemical performances. A new synthesis way consists in a facile fluorination reaction in aqueous HF solution followed by a moderate heat treatment at 230°C. Highly porous calisson-like particles with low crystallite sizes of 13-30 nm are obtained. Outstanding rate capability and cycling stability are observed. This material can deliver reversible capacities of 260 mAh g -1 at C/10 and 150 mAh g -1 at 2 C rate, as well as a stable capacity of 200 mAh g -1 at 1 C rate after 50 cycles. A systematic structural study at long range order by XRD and at the chemical bond scale by Raman microspectrometry reveals the crucial impact of nanosized particles on the Li ion insertion-extraction. The structural answer of nano-V2 O5 is found to produce a solid solution behavior over the largest Li composition range never reached for a Li intercalation compound (0 ≤ x ≤ 1.8). This result completely upsets the expected phase diagram for micro-Lix V2 O5 dominated by three wide biphasic regions. Such a finding explains the original sloped discharge-charge curves observed for nano-V2 O5 . Also we provide evidence for the better kinetics of Li insertion reaction induced by the nanosize effect of the material